Implementation of a Mental Health Screening Program in a Pediatric Tertiary Care Setting. (September 2019) - Herbert, Linda; Hardy, Steven
We evaluated the acceptability and usefulness of brief mental health screening during pediatric subspecialty clinic visits. Patients (8-17 years) and parents (of patients 5-17 years) in pediatric allergy, immunology, and hematology clinics completed the PROMIS (Patient-Reported Outcomes Measurement Information System) Pediatric Profile. Medical providers reviewed results and interpretations to guide discussion of mental health during visits. Almost all providers (96%) reported discussing mental health during visits but fewer parents (60%) said this discussion occurred. All parents who reported that mental health discussions occurred liked that this happened. Some parents (25%) who said no mental health discussion occurred wished it had. Most parents strongly agreed that screening completion was easy and appropriate. Most providers (79%) believed the screening was useful and 87% reported using screening results to guide discussion. Brief electronic mental health screening in pediatric subspecialty clinics is feasible, useful in guiding discussion, and viewed favorably by providers and parents of children with chronic illnesses.